Prognostic impact of red blood cell distribution width in pulmonary hypertension patients: A systematic review and meta-analysis. Issue 16 (April 2020) - Liu, Jie; Yang, Jiao; Xu, Shuanglan; Zhu, Yun; Xu, Shuangyan; Wei, Li; Qian, Panpan; Lv, Yuanyuan; Zhang, Chunfang; Xing, Xiqian; Deng, Yishu
Abstract : Abstract: Elevated red blood cell distribution width (RDW) may correlate with a worse prognosis in pulmonary hypertension (PH), though results to date are inconsistent. The goal of this study is to detect the impact of RDW on the prognosis of PH. PubMed and EMBASE databases were searched from their inception to July 22, 2019 for relevant publications reporting the relationship between RDW and the prognosis of PH. A meta-analysis was performed, and the heterogeneity across the included studies was evaluated using I 2 and Q statistics. We conducted sensitivity and subgroup analyses to detect sources of heterogeneity. In addition, potential publication bias was evaluated by Begg's and Egger's tests. In total, 1236 publications were retrieved, and 7 eligible publications with 666 PH patients were included in our meta-analysis. The results suggested that increased RDW can predict worse prognosis in PH (hazard ratio (HR) = 1.27, 95% confidence interval (CI) 1.11–1.45). According to subgroup analysis, study design, region, various endpoints, time of follow-up, and patient age were not sources of heterogeneity. In addition, RDW showed prognostic value in retrospective studies (HR = 1.32, 95%CI 1.15–1.51) but not in prospective studies (HR = 1.14, 95%CI 0.78–1.67). Additionally, RDW may serve as a predictive biomarker of PH in Europe (HR = 1.33, 95%CI 1.18–1.49) but not in Asia (HR = 1.20, 95%CI 0.90–1.58). Further analysis indicated that the prognostic value of RDW was influenced by patient age (>44 years: HR = 1.34, 95%CI 1.17–1.55; ⩽44 years: HR = 1.20, 95%CI 0.90–1.58) and follow-up (<3 years, HR = 1.36, 95%CI 0.53–3.47; ≥3 years, HR = 1.29, 95%CI 1.14–1.45). RDW provides important prognostic information for PH patients, and this measure may be used to optimize patient management and guide clinical treatment. PROSPERO registration number: CRD42019122636. Abstract : Supplemental Digital Content is available in the text